Influence of time-and-frequency indefiniteness of wide-range communication system - Паук, С. М.; Кавасмі, А. К. (Proceedings of National Aviation University (archive), 1998)
Considered is the model for estimation of time-and-frequency indefiniteness influence on efficiency of wide-range communication systems and the influence of quantity of wide-range signal position on signal system efficiency